Determinant Factors of Service Satisfaction In Integrated Service Posts - Alva Cherry Mustamu; Adriana Egam (Science Midwifery, 2021)
In Indonesia, the Integrated Service Post is the front line owned by the Public Health Center (PHC) as a primary service. However, sometimes there is a decrease in visits so that the quality of service decreases. The purpose of this study was to determine the factors that affect the satisfaction of Pos Pelayanan Terpadu services. This research is a quantitative study with a cross-sectional approach to 86 Integrated Service Post visitors in the working area of Malanu Public Health Center, Sorong city, West Papua, which were taken using purposive sampling. The instrument used in this study was an instrument of satisfaction, staff attitudes, knowledge, and family support. The results showed that there was an effect of staff attitudes and knowledge on satisfaction in Integrated Service Post services, but family support had no effect in determining the satisfaction of Integrated Service Post services. Service attitude and knowledge are major dimensions of overall satisfaction. PHC policymakers must evaluate and manage service quality based on actual patient needs, taking into account demographic characteristics and patient health status. Efficient management methods for PHC and Integrated Service Post, modern technology, and staff training are needed to improve service quality and care efficiency.